Odpowiedzi

Najlepsza Odpowiedź!
2010-03-12T17:57:20+01:00
1.Doprowadź wyrażenia do najprostszej postaci:
a)-(2a-3b+5)+4a-7b+3)-(3a-2b-1)=
-2a+3b-5+4a-7b+3-3a+2b+1= -a-2b-1
b)(4a+2b-7)-(a-3b-4)-(2a-b-3)=
4a+2b-7-a+3b+4-2a+b+3= a+6b-2
c)-(-2a-5b-4)+(2a-3b-4)-/9-3a-b+2)=
2a+5b+4+2a-3b-4-9+3a+b-2= 7a +3b -11
d)(-5a+b-3)-(2a-3b+5)-(4a-b-8) =-5a +b-3-2a+3b-5-4a+b+8= -11a +5b
Myślę, że pomogłam i zasługuję na naj;)

1 5 1
2010-03-12T17:58:59+01:00
1.Doprowadź wyrażenia do najprostszej postaci:
a)-(2a-3b+5)+4a-7b+3)-(3a-2b-1)
-2a+3b-5+4a-7b+3-3a+2b+1
-a-2b-1
b)(4a+2b-7)-(a-3b-4)-(2a-b-3)
4a+2b-7-a+3b+4-2a+b+3
a+6b-2
c)-(-2a-5b-4)+(2a-3b-4)-/9-3a-b+2)
2a+5b+4+2a-3b-4-9+3a+b-2
7a +3b -11
d)(-5a+b-3)-(2a-3b+5)-(4a-b-8)
-5a +b-3-2a+3b-5-4a+b+8
-11a +5b
1 5 1